2012
DOI: 10.1108/13639511211275805
|View full text |Cite
|
Sign up to set email alerts
|

Perceived experience and police officers’ ability to detect deception

Abstract: PurposeFor police officers, the ability to distinguish between truthful and deceptive statements in interrogations is essential. However, research shows that their classification accuracy is typically rather low. The purpose of this paper is to investigate the ability to detect deception as a function of perceived experience, in a sample of German police officers and police trainees.Design/methodology/approachThe authors had the participants judge ten video recordings of a mock crime with respect to the displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In all these studies, situational familiarity significantly improved the detection of deception for both fabricated and true accounts (overall from 8 to 22%, with d s ranging from 0.42 to 0.91), and the relative use of verbal content over nonverbal cues mediated the situational familiarity effect on accuracy. A new study by Reinhard, Dahm, and Scharmach (in press) found first evidence that perceived situational familiarity could improve the deception detection accuracy of police officers. In this study, police officers judged ten video recordings of a mock crime and judged the veracity of the displayed suspects’ behavior, who were accused of having stolen 20 EUR from a wallet.…”
Section: Discussionmentioning
confidence: 99%
“…In all these studies, situational familiarity significantly improved the detection of deception for both fabricated and true accounts (overall from 8 to 22%, with d s ranging from 0.42 to 0.91), and the relative use of verbal content over nonverbal cues mediated the situational familiarity effect on accuracy. A new study by Reinhard, Dahm, and Scharmach (in press) found first evidence that perceived situational familiarity could improve the deception detection accuracy of police officers. In this study, police officers judged ten video recordings of a mock crime and judged the veracity of the displayed suspects’ behavior, who were accused of having stolen 20 EUR from a wallet.…”
Section: Discussionmentioning
confidence: 99%
“…However, almost no study has focused on officers' processes in detecting deception, that is, the mechanisms and strategies they use to assess veracity. The findings of the few extant studies (Masip, Garrido, Herrero, Antón, & Alonso, ; Nahari, ; Reinhard, Dahm, & Scharmach, ) are limited because of being laboratory‐based, thus providing only behavioral—and not contextual—information to observers. In this study, officers were questioned about real lies they detected in real life.…”
Section: Contextual Deception Indicatorsmentioning
confidence: 99%
“…In Study 1, we used the stimulus material of Reinhard et al (2011, Study 1) who found higher accuracy levels when situational familiarity with the judgmental context was high. In another study using the same material, Reinhard, Dahm, and Scharmach (2012) found higher detection accuracy among police officers after inducing a feeling of being experienced in lie detection. In Study 2, we used the stimulus material of Dickhäuser et al (2012) who found higher accuracy levels when participants were instructed not to use stereotypical non‐verbal cues for their judgment.…”
Section: Discussionmentioning
confidence: 85%